Diagnosis and follow-up of patients with congenital hypothyroidism detected by neonatal screening - Amparo Rodríguez Sánchez; María J. Chueca Guindulain; María Alija Merillas; Susana Ares Segura; José Carlos Moreno Navarro; María Dolores Rodríguez Arnao (Elsevier, 2019)
The screening programme of congenital hypothyroidism (CH) is probably one of the best achievements in paediatrics. Thyroid hormones are essential for brain development and brain maturation that continue through the neonatal period. Hypothyroidism that begins in the first months of life causes irreversible damage to the central nervous system, and is one of the most frequent and preventable causes of mental retardation. As children with congenital hypothyroidism are born with a normal appearance, analytical studies are required to immediately start the appropriate therapy.This article analyses the aims, diagnostic procedures, tests required, aetiology, and differential diagnosis in this disorder. Especially relevant is to perform frequent monitoring to ensure dose adjustments of L-Thyroxine therapy, avoiding infra- or supra-dosing that negatively affects neurosensory functions. Re-evaluation of the aetiology permanent vs transient hypothyroidism is always recommended after 3 years of chronological age.The relevance of this screening programme should be widely discussed in paediatrics. The main objective is to avoid cerebral damage in these patients, and has been highly successful and economically beneficial.Other aspects are required to optimise patient outcomes, to perform all the controls according to the recommendations and to include, in the near future, the diagnosis of central hypothyroidism. Implementation of this programme is necessary to progress in accordance with current scientific knowledge. Resumen: El Programa de cribado o detección precoz del hipotiroidismo congénito (HC) es uno de los mayores avances logrados en Pediatría. Las hormonas tiroideas son imprescindibles para el desarrollo y la maduración cerebral, que continúan en la etapa neonatal. El hipotiroidismo de comienzo en los primeros meses de vida origina lesiones irreversibles en el sistema nervioso central y es una de las causas más frecuentes y evitables de retraso mental. El diagnóstico clínico es tardío, por lo que requiere estudio analítico para poder efectuar el tratamiento adecuado.Este artículo actualiza los objetivos, los procedimientos diagnósticos, las pruebas imprescindibles y complementarias requeridas, la etiología y los diagnósticos diferenciales en esta patología. Con especial énfasis en los requerimientos de los centros de seguimiento para protocolizar los resultados del tratamiento con L-tiroxina administrada de forma inmediata al diagnóstico y a las dosis que eviten fases de infra o supradosificación que pueden alterar diversos aspectos del desarrollo cognitivo. La revaluación de etiología permanente vs. transitoria se recomienda siempre después de los 3 años de edad.La relevancia de este programa precisa su difusión a todas las áreas de pediatría. El objetivo principal, evitar el daño cerebral en estos pacientes, se ha logrado y es además altamente beneficioso desde el punto de vista económico.Otros aspectos para optimizar los resultados cognitivos con todos los controles periódicos necesarios y lograr la inclusión del diagnóstico del HC central, precisan implementar los recursos de los centros de seguimiento y continuar avanzando según los conocimientos actuales.